Regional anesthesia for ambulatory pediatric penoscrotal procedures. Issue 6 (December 2021) - Osmani, Feroz; Ferrer, Fernando; Barnett, Natalie R.
Summary: Background/Purpose: Pediatric urology procedures are amongst the most commonly performed in children. The need for proactive treatment of pain is essential for optimal patient care. Current guidelines recommend the routine use of regional anesthesia in children as appropriate unless contraindicated. Given the commonality of urologic procedures in children, it is essential to understand the indications for and the utility of regional anesthesia. Methods: The current literature was searched using PubMed as the primary platform. Search words included 'dorsal penile nerve block, ' 'pudendal nerve block, ' 'ring block, ' 'spinal anesthesia, ' and 'caudal, ' along with 'pediatric', 'circumcision, ' 'hypospadias, ' 'urology', and 'urological surgery' as part of the keywords of the search. Results: The articles resulting from the literature search were reviewed for content, clarity and study design by two co-authors, and agreement determined the incorporation into the review. Additionally, a detailed description of study design, regional anesthetic technique, local anesthetic(s) used, and outcomes of each study referenced was incorporated into the supplemental table. Conclusion: Given the variance in block technique and local anesthetic choice amongst the current reported studies in the literature, it is difficult to truly compare and infer superiority of the regional anesthetic choices for ambulatory penoscrotal procedures. When choosing a regional anesthetic technique, careful consideration must be placed on block coverage, severity of expected pain and surgical duration of the procedure, type and dose of local anesthetic, as well as the patient's past medical history and anatomy. Moreover, the regional block chosen should result from a thorough preoperative discussion between the surgeon and the anesthesiologist.